Kelayakan dan Dampak Ekonomi-Ekologis Usaha Minuman Berbasis Susu: Studi Kasus Sticky Milk sebagai Inovasi Kewirausahaan Mahasiswa - Mohammad Afrizal Miradji; Bayuadi; Adheriana Wida Saputri; Amos Firdo Sihotang; Jea Nur Fitriana; Gunita; Fadensyah Muhammad Daffa Effendi (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study analyzes the business feasibility and sustainability dimensions of “Sticky Milk,” a student-led milk-based beverage enterprise developed at Universitas PGRI Adi Buana Surabaya. Using a qualitative descriptive approach supported by financial simulation, the research examines five aspects of business feasibility: market, technical, managerial, financial, and environmental-social impact. Field observations, interviews, and sales reports indicate that the product achieved strong consumer acceptance with a 13.2% profit margin and an estimated monthly net profit of IDR 750,000. The student team demonstrated efficient management, transparent financial records, and an environmentally aware production process using recyclable packaging. Socially, the project enhanced entrepreneurial skills, interdisciplinary collaboration, and local economic engagement within the campus community. These findings confirm that student entrepreneurship can integrate economic viability with ecological and social responsibility, forming a micro-scale model of green and circular business practice. The study proposes the development of green branding strategies, digital accounting, and supply-chain partnerships to ensure long-term sustainability.